PERAN ALAT BUKTI PENYADAPAN DALAM PERCEPATAN PEMBERANTASAN KORUPSI - Andari Dwi Utami (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Wiretapping by the KPK is used to obtain instructions for the KPK in proving a crime that is reported by the public in accordance with the authority given by law. Granting authority to wiretapping to the Commission is in a dilemma, on the one hand is needed to uncover corruption cases because the law must be able to follow the times and technology that can no longer rely on the evidence of conventional, on the other hand there are human rights that must be respected in enforcement law. This research aims to find out: 1) The regulation of the KPK's wiretapping authority in Law Number 19 of 2019 compared to the regulation in Law No. 30 of 2002, 2) The regulation of wiretapping as regulated in Law No.15 of 2019 is able to assist the KPK in conducting accelerated eradication of corruption. In this study the authors used a type of legal research with normative aspects consisting of primary legal materials, secondary legal materials and tertiary legal materials obtained through literature studies, primary legal materials here the KPK Law and the Revision of the KPK Law, and KUHAP. The wiretapping arrangements stipulated in Law No.15 of 2019 will be able to assist the KPK in carrying out its duties in the TPK investigation, if the appointed Supervisory Body also has a clear and firm and objective commitment in assessing and giving permission whether it is necessary to do wiretapping by the KPK in response to the report. and complaints from the public that go to the KPK, to eradicate corruption, because the implementation of wiretapping is now with the KPK and the KPK Supervisory Body. If the Supervisory Body does not have the commitment as referred to above, then corruption eradication by the KPK will be difficult to implement, because the TPK is usually carried out jointly with other parties, so proof is difficult without wiretapping.